Social responsibility and commitment in management institutes: mediation by engagement - Gupta, Manish; Sayeed, Omer (Business: Theory and Practice, 2016)
Due to its major influence on individual’s performance, engagement is increasingly becoming popular among practitioners. While its influence on performance has been well established, research on the influence of variables related to organizations on engagement is still in its nascent stage. Therefore, this study examines the mediating role of employee engagement in the corporate social responsibility (CSR) – organizational commitment relationship. Multiple regression results using responses from 150 academics working in Indian management institutes predominantly owned by business groups partially support the relationships hypothesized. The findings may encourage Indian management institutes owned by business groups to consider CSR in teaching and research as serious investment areas in order to have a more engaged and committed workforce.